Magnetic Resonance and Conductivity Study of Lead-Cadmium Fluorosilicate Glasses and Glass-Ceramics - Silva, Igor D.A.; Donoso, José Pedro; Magon, Claudio J.; Tambelli, Caio E.; Santagneli, Silvia H. [UNESP]; Ribeiro, Sidney J.L. [UNESP]; Silva, Mauricio A.P.; Chiesa, Mario; Rodrigues, Ana Candida M. (American Chemical Society (ACS), 2018)
The fluorine motional dynamics in fluorosilicate glasses and glass-ceramics of the SiO2-PbF2-CdF2 system was investigated by complex impedance spectroscopy and 19F nuclear magnetic resonance (NMR) spectroscopy, and the coordination environment of a Cu2+ paramagnetic probe was examined by electron paramagnetic resonance (EPR) spectroscopy. Glass-ceramics were obtained by heat treatment of glass at a temperature between the glass-transition (Tg) and the onset of crystallization (Tx). Ionic conductivity of about 1.6 × 10-4 S/cm was obtained at 500 K for glass. The conductivity of the glass-ceramics was found to be lower than that obtained for the glass. The temperature dependence of the 19F NMR spin-lattice relaxation times was investigated between 300 and 770 K. The 19F NMR results of glass exhibit the qualitative features associated with fluorine mobility, namely, the presence of a relaxation rate maximum below Tg. The NMR relaxation data of the glass-ceramics were analyzed assuming two fluorine dynamics. Continuous-wave EPR spectroscopy, using a Cu2+ ion as a probe, was employed to determine the local symmetry of the ion environment and the nature of relevant spin interactions. The hyperfine coupling of Cu2+ with the 19F, 113Cd, and 207Pb nuclei in the glass and the glass-ceramic was investigated by electron spin echo envelope modulation and hyperfine sublevel correlation spectroscopy.